Analysis of serum lactate level in septic shock at Emergency Department of Patan Hospital, Nepal - Batajoo, Kabita Hada; Thapa, Rashmi; Shrestha, Roshana; Shrestha, Ashis; Acharya, Samita; Bajracharya, Sumana (Journal of Kathmandu Medical College, 2017)
Background: Sepsis is a leading cause of death in emergency department. Serum lactate level assessment can play an important role for risk assessment and prognostication in critically ill septic patient. Objective: The objective of this study is to determine the relevance of initial serum lactate measurement after the implementation of sepsis protocol in emergency department, based on guidelines of Surviving Sepsis Campaign. Methods: This was a cross sectional descriptive study conducted at Patan Hospital from January 2014 to January 2015 among 94 sample of serum lactate who had clinical suspicion of sepsis as per established sepsis emergency department protocol. Data of serum lactate sent from emergency department was noted from the registry book of department of biochemistry, Patan Academy of Health Sciences. Based on clinical practice the obtained lactate results were stratified intothreerisk groups: high (> 4 mmol/L), intermediate (2.5 to 3.99 mmol/L) and low (< 2.5 mmol/L). Result: Out of the total 94 samples, 56 (59.6%) were male and 38 (40.4%) were female. Mean lactate level in males was 5.73 mmol/L and that in females was 5.47 mmol/L. Abnormal lactate level was predominantly high 85 (80%) out of which 31 (29%) had intermediate whereas more than half 54 (50.76%) had high lactate level. Conclusion: This study tells that clinically diagnosed sepsis do have higher serum lactate level. So, in our context, this needs to be explored to be used for early diagnosis of sepsis. Journal of Kathmandu Medical College Vol. 5, No. 2, Issue 16, Apr.-Jun., 2016, page: 49-51